2002
DOI: 10.1523/jneurosci.22-18-08277.2002
|View full text |Cite
|
Sign up to set email alerts
|

Selective Modification of Short-Term Hippocampal Synaptic Plasticity and Impaired Memory Extinction in Mice with a Congenitally Reduced Hippocampal Commissure

Abstract: The hippocampus is critical for forming new long-term memories, but the contributions of the hippocampal commissure (HC) to memory function and hippocampal synaptic plasticity are unclear. To shed light on this issue, we characterized behavioral memory and hippocampal synaptic plasticity in two inbred mouse strains. BALB/cWah1 mice display a range of corpus callosal defects and an intact HC, whereas 9XCA/Wah mice exhibit a complete absence of corpus callosum and a greatly reduced HC. No differences between str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 68 publications
1
30
0
Order By: Relevance
“…Notably, among multiple responses elicited by fear states, context-specific freezing has been proposed as one of the main risks factors for the development of anxiety disorders (Buss et al, 2004). Impaired extinction of freezing to contextual stimuli has been observed in mouse strains with reduced hippocampal commissure (Schimanski et al, 2002). Supporting this view, we have recently shown that hippocampal mechanisms encompassing actin rearrangement are required for contextual fear extinction (Fischer et al, 2004) in this paradigm.…”
Section: Introductionsupporting
confidence: 57%
“…Notably, among multiple responses elicited by fear states, context-specific freezing has been proposed as one of the main risks factors for the development of anxiety disorders (Buss et al, 2004). Impaired extinction of freezing to contextual stimuli has been observed in mouse strains with reduced hippocampal commissure (Schimanski et al, 2002). Supporting this view, we have recently shown that hippocampal mechanisms encompassing actin rearrangement are required for contextual fear extinction (Fischer et al, 2004) in this paradigm.…”
Section: Introductionsupporting
confidence: 57%
“…BTBR mice may prove especially valuable for investigating the role of the hippocampal commissure. The 9XCA/ Wah recombinant strain with severely reduced HC has an interesting deficit in paired-pulse facilitation of LTP in the hippocampal slice as well as slower extinction of con-textual conditioning [17]. If these deficits arise from the anatomical insufficiency of commissural inputs, then we would expect to observe similar deficits in BTBR.…”
Section: Discussionmentioning
confidence: 97%
“…fEPSPs were obtained by stimulating the Schaeffer collateral-commissural fibers with a bipolar nickel-chromium electrode (130 m diameter). Stimulation intensity (0.08 ms pulse duration) was adjusted to evoke fEPSP amplitudes that were 40% of maximal size (Schimanski et al, 2002;Woo and Nguyen, 2003). Subsequent fEPSPs were elicited at the rate of once per minute at this "test" stimulation intensity.…”
Section: Methodsmentioning
confidence: 99%